2008
DOI: 10.1080/02770900701840246
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Correlates of Overweight Status in Adolescent Asthma

Abstract: Background-Debate exists within the literature concerning whether asthma and obesity are linked as comorbid conditions. Further study is required to understand the relationship between asthma and overweight status, and developmental considerations are an important priority area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
15
2
Order By: Relevance
“…This is in contrast to the previous study in adolescent asthmatics that demonstrated a younger age of asthma onset in obese adolescents (18). However, this might be attributed to the relatively younger age group included in our study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…This is in contrast to the previous study in adolescent asthmatics that demonstrated a younger age of asthma onset in obese adolescents (18). However, this might be attributed to the relatively younger age group included in our study.…”
Section: Discussioncontrasting
confidence: 54%
“…However, they also did not detect a difference in asthma control measured by asthma control test between obese and non-obese asthmatics (6). A study on adolescents with asthma demonstrated that obesity was more frequent and that was associated with higher asthma morbidity (18). This has lead to the conclusion coexisting obesity and asthma cases a dual burden (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,21,22 This is further supported by the fact that weight loss studies have shown that obese patients with asthma who lose weight also show significant improvements in asthma morbidity. 22,23 The relationship between obesity and asthma-related outcomes is less clear, with some studies, [24][25][26][27][28] but not others, [29][30][31] suggesting that obese children with asthma have worse asthma outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…31 However, unlike our study, other studies suggest that obese children with asthma have worse asthma morbidity and greater health care utilization, including being more likely to be prescribed 3 or more asthma medications and to have more days with wheezing, more ED visits, and more hospitalizations. [24][25][26][27][28]46 Recently, in a cross-sectional study examining the electronic medical records of adolescents enrolled in an integrated health plan where approximately 74,000 children had current asthma, Black et al found that extremely obese youth had higher rates of asthma-related ambulatory care visits and ED visits compared with normal weight youth. 46 One reason that obesity may have been associated with worse asthma morbidity and greater health care utilization in some studies, but not others (including ours), may have to do with the variability of asthma control and morbidity.…”
mentioning
confidence: 99%